Аспекти реставрації голови лева з виногроном в кам’яниці на вулиці Руській, 4 у Львові - Рибчинський, О. В.; Rybchynskyi, O. (Видавництво Львівської політехніки, 2019)
У статті розкрито методику реставрації, а також архітектурні, конструктивні та мистецькі особливості голови лева з виногроном. Викладено аргументи на користь твердження, що завдяки деталям можна репрезентувати просторовий образ Львова у культурному контексті вибраних століть.

Article describes the methods of restoration, as well as the architectural, constructive and artistic features of head of a lion with vineyard. Expounded arguments in favor of the claim that because of details can represent the spatial image of the city in the cultural context of selected ages. Before the restoration works, the stone carving was in unsatisfactory condition: numerous caverns and chips, head of the lion has cross-cutting cracks.State of cracks threatened to split into seven parts, vineyard ran out of the mouth. On the surface of the stone were dense and strong pollution and black “wild” patina. On the carved plastic of the head are extensive colonies of mosses and lichens, groats and putty portlan-cement, layering of bird droppings. The console with carved plating has numerous mechanical damage and loss from chiseling. The stone blocks of the arch were poptute with a large number of chips and cracks, cement tiles and shutters, deep shavings from electric wires. The stone used in the laying of the arch and the console were in a state of average structural strength, but the head of the lion due to the dense overgrown moss. On the head of the lion, the console and the side blocks are extensive spots of caustic yellow paint. Before the start of the restoration works, the wall was covered a cemented-sand smelting around them. The program of restoration measures provided for: 1) the execution of the vibration around the head, the console and the stone masonry arch in order to limit the touch of cement to the monument; 2) cleansing the head from colonies of mosses and lichens; 3) clearing of stone from Portland cement tiles and putty; 4) dismantling of vine and crushed and cracked brick-cement support under the jaw; 5) cleansing and gluing parts of the jaw and mane; 6) purification from portland cement and removal of a rusty metal wire from vine and sticking its fragments; 7) clearing of the authentic iron anchor of grapevine from corrosion and its polymeric varnishing; 8) installation of a thin white stone wall (5 cm thick) in the lion's mouth and attaching it to the vine; 9) installation of limestone stone block bearing with a head and a console; 10) extraction of lost parts and chips of a stone masonry arch; 11) injecting cracks and gluing the reflected parts of the stone; 12) visualization of the archway masonry important for perception; 13) restoration accentuation of profiled blocks and a trace from the construction of the cover of the staircase hole in the brewery; 14) the implementation of antiseptic compress on the head of a lion; 15) structural strengthening of limestone with an organosilicon reinforcement; 16) forestry of precipitated fragments; 17) conservation of the metal ring; 18) covering the head of the lion, the console and the lower parts of the arch with a biocidal solution. During the work turned out that the inner part of the stone blocks of the arch has a black "wild" patina, which testified to their reuse. The head of a lion was in the middle of a hollow, square in a slit, with a wall thickness of 4 to 8 cm. Inside the cheeks there are longitudinally carefully carved grooves. On the inner walls there are traces of carving chisels. The eyes of the lion with the through holes, which began with the inner large cavity. The length of the preserved head reached one meter. The head of a lion with a vinegar, a console with profiles and a wicker plate testify to the ancient craftsmanship, technology and school of stone processing. Young restorers play an important role in discovering the unknown pages of the city's architecture. They fill the empty gaps, make puzzles, form a private, individual image of the city in the collection of lapidary Lviv. Structure of the stone, stylistics and carver's handwriting indicate that the lion and console are timeconsuming, and also come from separate buildings. The head of the lion in the past was intended for spillage, and the inner part of the gut was presumably of copper plaque which was fixed in the retained lateral grooves. The console with a wicker was previously part of a frieze composition that decorated the facade of the building. After performing restoration work is necessary to continue research on the history of the origin of the monument, as well as to check the state of conservation under the influence of the environment.
Aspects of restoration lion`s head with bunches of wine in a stone house on Ryska street, 4 in Lviv
Keywords: реставрація; голова лева; кам’яниця; Львів; restoration; lion's head; stone building; Lviv; 72.02